Mothers’ knowledge, attitudes and perceptions on children less than 3 year-old nutrition in a Lima’s community - Gamarra-Atero, Raquel (2010)
Introduction: To adopt a conduct it is necessary to identify internal factors that affect it. Objectives: To identify mothers´ knowledge, attitudes and perceptions on children less than 3 year-old nutrition. Design: Quantitative qualitative study, descriptive, exploratory. Location: Villa Maria del Triunfo Human Settlements, Lima, Peru. Participants: Mothers of children less than 3 year-old. Interventions: Following informed consent, for the quantitative phase phase we applied a questionnaire of 10 closed questions with dichotomous responses on knowledge and 10 questions with Likert’s response categories on attitudes to 161 mothers; and for the qualitative we did 28 depth interviews and 4 focus groups to identify perceptions were conducted to 68 mothers. Main outcome measures: Level of knowledge, type of attitudes and perceptions on breastfeeding (BF), complementary feeding (CF) and feeding during illness. Results: Eighty-one per cent of participants showed high level of knowledge, 65% showed complete agreement with exclusive BF during the first 6 months, 63% agreed with adequate complementary feeding practices. Most felt that BF should be offered up to 2 years because it helps organs development and the children to grow up healthy. CF should be started at six months of age because it helps the stomach function, the child has more appetite and BF is no longer sufficient; consumption of animal foods, fruits and vegetables should be daily; during diarrhea plenty of fluids and more frequent food and in smaller amounts should be provided. Conclusions: Mothers showed high levels of knowledge (81%), favorable attitudes (66,7%) on infant feeding and their perceptions in general agreed with it.